Propuesta didáctica basada en actividades lúdico - recreativas para la enseñanza de capacidades coordinativas, en estudiantes de octavo de básica - Quishpe Panimbosa, Juan Daniel (2024)
The problem deals with this present study is focused on teaching of physical coordination abilities for eight grade students of Rosario del Alcazar high school through playful recreational activities. It was done a meticulous investigation to know the causes of unsuitable teaching-learning process of coordination abilities as well as the lack of methodological innovative strategies by physical education educators. The kind of investigation that was used is a mixed approach as it was applied a survey and coordination test in a sample of 32 students, 2 administrative workers, 7 teachers of upper basic education and 1 teacher of physical education area. Among of main results was found both teachers and students take into consideration that the practice of playful recreational activities are an alternative to generate much student’s interest and to facilitate the teaching-learning process. For this reason, it was done a didactic proposal with playful-recreational activities that will allow to work with each coordination ability which will be applied during seven weeks. In conclusion, this didactic proposal will help students and educators to know about the importance of coordination activities within daily life, moreover, their relevance in sporting practice.